2001
DOI: 10.1096/fj.99-0934com
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix protein 1 (ECM1) has angiogenic properties and is expressed by breast tumor cells

Abstract: Tumor growth and metastasis are critically dependent on the formation of new blood vessels. The present study found that extracellular matrix protein 1 (ECM1), a newly described secretory glycoprotein, promotes angiogenesis. This was initially suggested by in situ hybridization studies of mouse embryos indicating that the ECM1 message was associated with blood vessels and its expression pattern was similar to that of flk-1, a recognized marker for endothelium. More direct evidence for the role of ECM1 in angio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
76
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(81 citation statements)
references
References 22 publications
4
76
0
1
Order By: Relevance
“…ECM1 is a secreted glycoprotein reportedly involved in bone formation [22], in endothelial cell proliferation, and in the promotion of angiogenesis [23], but its function is best studied in basement membrane physiology. ECM1 has been shown to interact specifically with perlecan, a major heparan sulfate proteoglycan of basement membranes [24] and loss of ECM1 function in humans is responsible for lipoid proteinosis, a rare, autosomal recessive skin disorder which involves widespread hyaline deposition and the disruption/reduplication of basement membranes [25].…”
Section: Protein Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…ECM1 is a secreted glycoprotein reportedly involved in bone formation [22], in endothelial cell proliferation, and in the promotion of angiogenesis [23], but its function is best studied in basement membrane physiology. ECM1 has been shown to interact specifically with perlecan, a major heparan sulfate proteoglycan of basement membranes [24] and loss of ECM1 function in humans is responsible for lipoid proteinosis, a rare, autosomal recessive skin disorder which involves widespread hyaline deposition and the disruption/reduplication of basement membranes [25].…”
Section: Protein Identificationmentioning
confidence: 99%
“…ECM1 has been shown to interact specifically with perlecan, a major heparan sulfate proteoglycan of basement membranes [24] and loss of ECM1 function in humans is responsible for lipoid proteinosis, a rare, autosomal recessive skin disorder which involves widespread hyaline deposition and the disruption/reduplication of basement membranes [25]. Analysis of expression of ECM1 in a panel of human tumors found that it was closely correlated with some types of tumors, including breast carcinoma [23], gastric cancer and colorectal cancer. Furthermore, ECM1 expression correlated with the metastatic potential of tumors in one study.…”
Section: Protein Identificationmentioning
confidence: 99%
“…It is able to enhance the proliferation of endothelial cells during angiogenesis [44] and inhibit MMP-9 proteolytic activity [45]. Louridos et al observed that the level of ECM-1 secreted by cells originating from damaged OA cartilage is 3-fold higher than that of healthy cartilage [13].…”
mentioning
confidence: 99%
“…The biological function of ECM1 is not fully elucidated, but indications for its involvement in important processes like skin differentiation, endochondral bone formation and angiogenesis were found [5,10,11]. We have recently described the role of ECM1 in angiogenesis and its *Address correspondence to this author at the Department of Biomedical Sciences, University of Antwerp, Laboratory of Molecular Biotechnology, Campus Drie Eiken, Universiteitsplein 1, 2610 Wilrijk, Belgium; Tel: 32-3-8202311; Fax: 32-3-8202239; E-mail: joseph.merregaert@ua.ac.be implications in cancer biology [12], while its putative function in the molecular pathology of lipoid proteinosis (LiP) has been reviewed by Chan [13,33].…”
Section: Introductionmentioning
confidence: 99%